Challenges and innovations in resistance, remediation, and regulation: key findings from the spring 2025 ASM Theobald Smith Society meeting - Lily Lumkong; Brian Nyiro; Sammi Russo; Isabella Westervelt; Raymond F. Sullivan; Jeffrey M. Boyd; Valerie J. Carabetta; Srujana S. Yadavalli; Jennifer S. Sun (mSphere)
ABSTRACT The annual spring meeting for the Theobald Smith Society was held in May 2025 on the campus of Rutgers University—New Brunswick, as part of a 2-day celebration of microbiology discovery in New Jersey. A total of 140 branch members from across New Jersey attended the meeting, composed of undergraduate, graduate, and postdoctoral trainees, faculty members, and government and industry professionals. This report highlights the breadth and diversity of research conducted by members of the American Society for Microbiology in the Theobald Smith Society and celebrates their groundbreaking discoveries.